A Multispecific Investigation of the Metal Effect in Mammalian Odorant Receptors for Sulfur-Containing Compounds. (6th April 2018) - Zhang, Ruina; Pan, Yi; Ahmed, Lucky; Block, Eric; Zhang, Yuetian; Batista, Victor S; Zhuang, Hanyi
Abstract: Metal-coordinating compounds are generally known to have strong smells, a phenomenon that can be attributed to the fact that odorant receptors for intense-smelling compounds, such as those containing sulfur, may be metalloproteins. We previously identified a mouse odorant receptor (OR), Olfr1509, that requires copper ions for sensitive detection of a series of metal-coordinating odorants, including (methylthio)methanethiol (MTMT), a strong-smelling component of male mouse urine that attracts female mice. By combining mutagenesis and quantum mechanics/molecular mechanics (QM/MM) modeling, we identified candidate binding sites in Olfr1509 that may bind to the copper–MTMT complex. However, whether there are other receptors utilizing metal ions for ligand-binding and other sites important for receptor activation is still unknown. In this study, we describe a second mouse OR for MTMT with a copper effect, namely Olfr1019. In an attempt to investigate the functional changes of metal-coordinating ORs in multiple species and to decipher additional sites involved in the metal effect, we cloned various mammalian orthologs of the 2 mouse MTMT receptors, and a third mouse MTMT receptor, Olfr15, that does not have a copper effect. We found that the function of all 3 MTMT receptors varies greatly among species and that the response to MTMT always co-occurred with the copper effect. Furthermore, using ancestral reconstruction and QM/MM modeling combined with receptor functional assay, we found that the amino acid residue R260 in Olfr1509 and the respective R261 site in Olfr1019 may be important for receptor activation.